2018
DOI: 10.1061/(asce)mt.1943-5533.0002206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Aging Methods on Chemical and Rheological Properties of Bitumen

Abstract: Bitumen undergoes ageing, which leads to changes in its chemical and rheological properties, thus becoming harder and more brittle in time. This study aims to compare the effects of different laboratory ageing methods on chemistry and rheology of three bitumen types, i.e. a Pen 40/60, a Pen 70/100 and a polymer modified bitumen (PmB). Four ageing protocols were applied: ageing at room temperature, oven ageing, the Pressure Ageing Vessel (PAV), and the Rolling Thin Film Oven Test (RTFOT) combined with PAV agein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…Nevertheless, temperature was found to be the most influential parameter for ageing, probably because the ageing rate coefficient increases exponentially with temperature based on the Arrhenius equation. Detail on the effect of the ageing parameters on the rheology of the studied bitumen type are discussed in previous studies (Jing et al 2018, Tarsi et al 2018. Black diagrams, Figure 2, were plotted to present the rheological changes of bitumen with ageing.…”
Section: Frequency Sweep Testsmentioning
confidence: 97%
“…Nevertheless, temperature was found to be the most influential parameter for ageing, probably because the ageing rate coefficient increases exponentially with temperature based on the Arrhenius equation. Detail on the effect of the ageing parameters on the rheology of the studied bitumen type are discussed in previous studies (Jing et al 2018, Tarsi et al 2018. Black diagrams, Figure 2, were plotted to present the rheological changes of bitumen with ageing.…”
Section: Frequency Sweep Testsmentioning
confidence: 97%
“…Carbonyl compounds and sulfoxides are commonly formed during the chemical transformations caused by oxidative aging. Therefore, to quantitatively analyze the changes of specific functional groups due to the aging effects, the peak areas under the specific band were measured from valley to valley at specifically selected wavenumbers of the obtained spectrum [24].Two aging related indices, the carbonyl index (I C¼O ) and ) were also calculated to monitor the evolution of chemical constituents of binder during aging [8].…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…The sum of carbonyl index and sulfoxide index was used as the combined chemical aging index of bitumen after aging [36]. It is noteworthy that although aromaticity index of a binder is closely related to its mechanical properties [37], the relationship between aromaticity level and aging state is not well-defined as the carbonyl or sulfoxide index [8]. Therefore, the correlation was not done between aromaticity and mechanical parameters.…”
Section: Chemo-mechanics Of Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have investigated the effect of ageing on rheological and chemical properties of asphalt binders (e.g. Feng et al, 2013;Leiva-Villacorta et al, 2014;Lu & Isacsson, 2002;Molenaar et al, 2010;Osmari et al, 2017;Osmari et al, 2018;Petersen, 2009;Qin et al, 2014;Takahashi et al, 2019;Tarsi et al, 2018;Wang et al, 2015;Zhang et al, 2018). A review of laboratory protocols to test asphalt binder ageing can be found in Wistuba and Renken (2011).…”
Section: Introductionmentioning
confidence: 99%